Injectable agarose hydrogels and doxorubicin-encapsulated iron-gallic acid nanoparticles for chemodynamic-photothermal synergistic therapy against osteosarcoma - Ying, Hongliang; Wang, Haitian; Jiang, Guangchuan; Tang, Han; Li, Lingrui; Zhang, Jinrui (Frontiers in Chemistry, 2022)
Osteosarcoma is a malignant bone cancer that usually occurs in children and adolescents. Although chemotherapy, radiotherapy and other methods have been used to treat osteosarcoma, these therapeutic regimens fail to cure this disease completely. Herein, doxorubicin-encapsulated iron–gallic acid (FeGA-DOX) nanoparticles (NPs) were fused with agarose hydrogels (AG) for synergistic therapy of osteosarcoma. Under near-infrared laser irradiation, the local temperature of FeGA-DOX NPs was increased. Therefore, tumour cells were killed using photothermal therapy, and AG dissolved to release FeGA-DOX into the cells. Doxorubicin generates hydrogen peroxide, which is then converted to reactive oxygen species (ROS) via FeGA-DOX by the Fenton reaction, inducing tumour cell apoptosis. ROS induced by chemodynamic therapy compensates for the incomplete cure of osteosarcoma cells. The AG-encapsulated NPs could mediate synergistic chemodynamic and photothermal therapy with self-sufficient H2O2, providing a novel therapeutic strategy for osteosarcoma.